Bedside computer access for an individual with severe and multiple disabilities: a case study. - Blain S; McKeever P; Chau T (Disability & Rehabilitation: Assistive Technology, 2010)
Purpose. This case study documents the process of designing a custom-tailored bedside computer access solution for a 20-year old individual with quadriplegia and reports the effects of computer access on her participation in life activities. Method. We adopted a person-focused approach to match the individual to an access solution. Two months after the access solution's introduction, we measured its impact using a 2-dimensional Fitt's Law test and questionnaire from the ISO 9241-9 standards document, typing tests, a usage log and a semi-structured interview. The Canadian Occupational Performance Measure was also administered pre- and post- access, focusing on the client's perceived ability to use the computer. Results. After 2 months, the individual was spending an average of 8.4 h per day on the computer, engaging in electronic communication, recreational, and educational activities. She learned single-switch typing with a throughput of 1.03 bits/s and targeting accuracy of 87.5%. The questionnaire revealed that the client was thoroughly satisfied with the interface. These results were interpreted as positive gains in the International Classification of Functioning, Disability and Health domains of communication and social interaction. Conclusions. By addressing individual goals, abilities and relevant environmental factors, a bedside computer access solution can be developed for individuals in long-term care. The introduction of a computer access solution augmented the participant's communication, leisure and educational activities, as well as perceived independence.